Prolegomena to Metaphysics of Education as Noetics - Janas, Adam (Paedagogia Christiana, 2026)
The considerations undertaken in the article concern education as an ideational area of all reflective pedagogical practice. This practice can be conceptualised in the form of theory, philosophy and metaphysics of education. The concept of the metaphysics of education as noetics will be proposed, i.e. such a practice of pedagogical thinking that relates the thinking of education beyond itself, to what precedes, enables and justifies it. The intellectual background of the considerations undertaken will be the contemporary paradigm of research on Plato’s philosophy. The principle role of education will turn out to be transcendence, as the ontological emancipation of man towards the unity of what is immanently – biopsychosocially, historically and culturally – differentiated. Finally, a conceptual illustration of the metaphysics of education as noetics will be presented in the form of Viktor Frankl’s pedagogical-philosophical concept of ‘ontology of dimensions.’